Il rilievo dei prati stabili come indicatore della qualità delle banche dati - Negro, Andrea (GEOmedia, 2013)
Dal rilievo sul campo al confronto con la realtà dei più comuni e usati database regionali per individuarne criticità e punti di forza attraverso strumenti GIS. From the survey in the field to the comparison with the reality of the most common and regional databases used to identify critical issues and strengths through GIS tools. The survey conducted has focused primarily on permanent grassland, agricultural areas which maintain this characteristic in time and destination of use, which allows an assessment of the quality of different databases under consideration. The monitoring activity was performed in the Lombardy Region, entity with an Infrastructure for Spatial Information (II T), which through its geo-portal enables access to databases aimed at the analysis of vector and raster different spatial and environmental components.